The effect of pullout timing on breaststroke turn performance - Alcock, A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
In swimming races, between 20 and 40% of the total event time is spent turning (Thayer & Hay 1984; Blanksby et al. 1998). Therefore turns are an important consideration for performance because an improvement in turning technique could improve event time and placing. Of the four competitive swimming strokes, breaststroke turn times are the slowest and most variable, and Newble (1982) suggested that this was likely a result of the greater technical expertise required. Breaststroke turns also involve longer breakout distances and breakout times compared with the other strokes (Chow et al. 1984). According to the international swimming federation rules for breaststroke, 'After each turn, the swimmer may take one arm stroke completely back to the legs during which the swimmer may be submerged. A single butterfly kick is permitted during the first arm stroke, followed by a breaststroke kick. The head must break the surface of the water before the hands turn inward at the widest part of the second stroke' (FINA 2012, p. 167). The timing and execution of these aspects of the turn could all affect the final race time. During a breaststroke turn, swimmers push off the wall with both feet which allows them to travel at a higher velocity than they can actually swim the breaststroke. Following the push-off, they adopt their most streamlined position to minimise their drag and rate of deceleration, and thus maintain this higher velocity for as long as possible. Theoretically, the optimal breaststroke pullout is one in which the swimmer maximises the amount of time they travel above the velocity at which they can swim, and minimises the time spent below the velocity at which they can swim breaststroke. This is because if they travel for too long below their average free-swimming velocity, it would be faster for them to be actually swimming. The aim of this study was to determine the effect of the timing of the breaststroke pullout on overall turn performance.